73: HOSPITAL EMERGENCY RESPONSE AGAINST DISASTERS: EVIDENCE FROM HOSPITALS IN IRAN. (8th February 2017) - Janati, Ali; Sadeghi-bazargani, Homayoun; Hasanpoor, Edris; Sokhanvar, Mobin; HaghGoshyie, Elaheh
Abstract : Background and aims: Hospitals play a critical role in providing communities with essential medical care during all types of disaster. Hospital emergency management is a continuing process requiring the monolithic integration of planning and response attempts with local and national schemes. The aim of the current study was to assess emergency response of hospitals against disasters in Tabriz. Methods: A cross-sectional study was conducted in Tabriz city, during 2016 in Iran. The study population included all hospitals in Tabriz city. 18 hospitals were assessed. Hospital emergency response checklist was used to collect data. Tool components including: Command and control, Communication, Safety and security, Triage, Surge capacity, Continuity of essential services, Human resources, Logistics and supply management and Post-disaster recovery. Data entry and analysis was done using SPSS-20. Results: The results showed that emergency response of hospitals were 54.26 percent in Tabriz. The lowest response rates were related to Shafaa hospital (18.89%) and highest response rates was related to Razi hospital (91.67%). Components of hospital emergency response were assessed between 48.07% (Surge capacity) to 58.95% (Communication). Conclusion: Based on WHO checklist, the only emergency response of hospitals were 54.26 percent in Tabriz. So, Hospital emergency responses against disasters have to be improved and should be 100 percent. It is essential to design a comprehensive framework for hospital emergency response.